Nanomotor‐Based Strategy for Enhanced Penetration across Vasculature Model. (15th January 2018) - Peng, Fei; Men, Yongjun; Tu, Yingfeng; Chen, Yongming; Wilson, Daniela A.
Abstract: Here the first nanomotor‐based strategy is reported to effectively cross tumor vasculature endothelium. The designed nanomotors are based on (poly(ethylene glycol)‐ b ‐polystyrene and poly(acrylic acid)‐ b ‐polystyrene) building blocks, which further self‐assemble into polymersomes of tunable sizes (100, 300 nm). The polymersomes are readily loaded with hydrophilic model drug into the aqueous compartment. A catalytic platinum cap is then partially deposited on the surface of the polymersome via electron beam evaporation, resulting in a polymersome Janus nanomotor. In a tumor vasculature model, these cargo‐loaded polymersome nanomotors demonstrate enhanced penetration across the endothelium. Abstract : A polymersome‐based Janus nanomotor is developed with a versatile fabrication approach . With its hollow cavity, the polymersome nanomotor is capable of carrying model drug cargo. The nanomotor exhibits enhanced penetration across the tumor vasculature model and capable of release cargo on demand. The nanomotor provides a promising platform for active cargo delivery using the enhanced permeability and retention (EPR) strategy.